The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1466-7657.2007.00572.x
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive methods with male participation: a perspective of Brazilian couples

Abstract: Specific actions are necessary for men to achieve integral participation in relation to reproductive sexual health. These include education and discussions on gender roles, leading to greater awareness in men of the realities of sexual and reproductive health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Therefore we suggest a consultation and specific educational programs for both males and females. Similar findings were reported in several previous studies [20-22]. …”
Section: Discussionsupporting
confidence: 93%
“…Therefore we suggest a consultation and specific educational programs for both males and females. Similar findings were reported in several previous studies [20-22]. …”
Section: Discussionsupporting
confidence: 93%
“…Tanzanian women suggested that vasectomy would eliminate the possibility of having a child out of wedlock 29 , 30 . In addition, Brazilian, 38 Indian, 22 Rwandan, 39 – 41 and Tanzanian 29 , 30 men described how vasectomy was beneficial to preserving the health of women (e.g., by avoiding frequent pregnancies and negative impacts of other forms of contraception) and that it was considered a minor procedure compared with female sterilization. Hearing positive testimonials was one of the main drivers of positive attitudes toward vasectomy in India—women felt encouraged and men were more open to the procedure 22 …”
Section: Resultsmentioning
confidence: 99%
“…The perception that male condoms hinder sexual spontaneity and enjoyment is well known [39], and long-term methods such as vasectomy are not appropriate for couples who intend to conceive in the future. On the one hand, such requests reveal the unmet need of male fertility regulation methods, at least among men who are not opposed to family planning.…”
Section: Discussionmentioning
confidence: 99%
“…Proposing more options for male-controlled contraceptives may reflect men’s desire to have greater influence in matters of reproductive health than is possible with female-controlled methods. Research in other settings has suggested as well that men’s opposition to family planning is a self-protective concern for themselves, rather than their partners, to mitigate suspicions of extramarital relations [39]. …”
Section: Discussionmentioning
confidence: 99%